2010
DOI: 10.1007/s11999-010-1456-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the Emotional Acceptance After Limb Salvage with an Expandable Prosthesis?

Abstract: Background Limb preservation surgery for extremity sarcomas offers the promise of improved function and cosmesis over amputation. Application of limb salvage surgery for pediatric patients with expandable metallic endoprostheses is gaining acceptance. The few studies reporting these devices have focused on functional outcomes; one has addressed quality of life. Questions/purposes We asked the following questions: (1) how happy are these patients; (2) how do these patients perceive their bodies; (3) do these ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…In addition, children tend to be more active than adults and may be less compliant with activity restrictions [26]. Overall we observed fewer complications with the nonsurgical lengthening prostheses, however, this limited series and those in the literature cannot provide statistical justification of one device over another [8,9,15,16,18,20,24,25,28,31]. When considering inflation, the maintenance reimbursements for our noninvasive lengthening devices were similar to that reported by Grimer et al, albeit with less followup [14].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, children tend to be more active than adults and may be less compliant with activity restrictions [26]. Overall we observed fewer complications with the nonsurgical lengthening prostheses, however, this limited series and those in the literature cannot provide statistical justification of one device over another [8,9,15,16,18,20,24,25,28,31]. When considering inflation, the maintenance reimbursements for our noninvasive lengthening devices were similar to that reported by Grimer et al, albeit with less followup [14].…”
Section: Discussionsupporting
confidence: 73%
“…Median Musculoskeletal Tumor Society (MSTS) functional scores of 80 have been reported in this population [1,13]. Mean patient satisfaction, measured with the Pediatric Outcomes Data Collection Instrument (PODCI), has been reported to range from 80 to 90 [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, we routinely perform growth estimates using the charts of Anderson et al, 32 after an estimation of bone age on the basis of the Atlas of Greulich and Pyle, 33 because we consider this method as the most reliable and practical method to estimate the growth anticipated in the contralateral limb and expected growth loss from resection of a physis and make decisions referable to equalization procedures. 1,[17][18][19][20][21][22][23][24][25][26]29,49,50 Children and parents have a high level of emotional and cosmetic acceptance because it is thought to be more "normal" than other options. 40 The reported 10-year survival rates of 70% to 80% 21,41-44 and local recurrence rates of 5% to 10% 41,42,45 have been comparable with those after amputation.…”
Section: Discussionmentioning
confidence: 99%
“…8,13,14 The longer the segment to be replaced, the higher the incidence of complications 6 ; in addition, the immunosuppressive effect of chemotherapy and radiation therapy and the increased complications rates associated with these treatment options following limb-salvage surgery are well documented. [17][18][19][20][21][22][23] However, open lengthening procedures for the invasive lengthening designs were accompanied by the risk of ankylosis, nerve damage, and infection. 2 Previous studies reported satisfactory results with expandable prostheses in children, offering the advantages of limb-salvage in addition to total lengthening up to 19.5 cm, and good or excellent Musculoskeletal Tumor Society (MSTS) functional results were observed at a follow-up of up to 12 years.…”
mentioning
confidence: 99%
“…In 2010, Henderson et al studied the emotional acceptance of limb salvage with expandable prostheses in children, concluding that the level of happiness is similar to patients without tumor and have a good level of social functioning [18].…”
Section: Discussionmentioning
confidence: 99%